Advancing freeze desalination through ultrasound-enhanced modelling: Case studies and insights for commercial applications - Symeon Savvopoulos; Anas AL-Aghbari; Khadije El Kadi; Denys Dutykh; Isam Janajreh (Case Studies in Thermal Engineering)
Freeze desalination is a promising alternative to conventional methods, offering energy-efficient and environmentally friendly solutions for freshwater production. This study presents theoretical modeling of a crystallizer to investigate the dynamics of continuous freeze desalination enhanced by ultrasound vibrations. A mathematical framework combining Navier-Stokes perturbation analysis with crystallization kinetics analyzes the interplay between fluid flow, heat transfer, and crystal growth under varying conditions. The model provides rapid, reliable predictions to support commercial scalability. Results show that increasing vibration velocity amplitudes and extending residence time improve both crystal growth and desalination efficiency. For example, at a vibration velocity amplitude of 12 m/s and a residence time of 135 s, desalination efficiency approaches 50 %, highlighting ultrasound's role in enhancing salt exclusion and crystallization rates. Temperature profiles along the crystallizer indicate that longer residence times allow greater cooling and impurity rejection, with freezing temperatures near the mushy zone approaching the eutectic point. The framework supports the design of scalable systems and fast control strategies to mitigate disturbances, maintain stability, and respond to variable freshwater demands. By linking theoretical modeling with experimental insights, this study advances the development of efficient, commercially viable freeze desalination technologies, offering a sustainable approach to addressing global water scarcity.